Workability and strength of lignite bottom ash geopolymer mortar - Apha Sathonsaowaphak (2018)
In this paper, the waste lignite bottom ash from power station was used as a source material for making geopolymer. Sodium silicate and sodium hydroxide (NaOH) were used as liquid for the mixture and heat curing was used to activate the geopolymerization. The fineness of bottom ash, the liquid alkaline/ash ratio, the sodium silicate/NaOH ratio and the NaOH concentration were studied. The effects of the additions of water, NaOH and napthalene-based superplasticizer on the workability and strength of the geopolymer mortar were also studied. Relatively high strength geopolymer mortars of 24.0-58.0 MPa were obtained with the use of ground bottom ash with 3% retained on sieve no. 325 and mean particle size of 15.7 μm, using liquid alkaline/ash ratios of 0.429-0.709, the sodium silicate/NaOH ratios of 0.67-1.5 and 7.5-12.5 M NaOH. The incorporation of water improved the workability of geopolymer mortar more effectively than the use of napthalene-based superplasticizer with similar slight reduction in strengths. The addition of NaOH solution slightly improves the workability of the mix while maintaining the strength of the geopolymer mortars. © 2009 Elsevier B.V. All rights reserved.